Pengembangan Model Pembelajaran Matematika Sekolah Dasar Berbasis Pendekatan Kontekstual untuk Meningkatkan Literasi Numerasi - Abdul Majid (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This study aims to develop a contextual-based mathematics learning model for elementary schools to improve students’ numeracy literacy. The study was motivated by the low level of numeracy literacy among students, caused by abstract instructional practices that insufficiently connect mathematical concepts with real-life contexts. This research employed a Research and Development (R&D) method consisting of needs analysis, model design, product development, expert validation, limited trials, field testing, and product revision. The study was conducted in October 2025 at SDN 50 Bono Panno, Pangkep Regency, involving elementary school students and classroom teachers as research participants. The research instruments included expert validation sheets, teacher and student response questionnaires, observation sheets of learning implementation, and numeracy literacy tests (pretest and posttest). Data were analyzed using descriptive quantitative and qualitative methods as well as inferential statistical tests to determine learning improvement. The expert validation results showed an average score of 3.65, categorized as highly valid. The practicality test based on teacher and student responses reached 88%, categorized as highly practical. The effectiveness test indicated a significant improvement in students’ numeracy literacy, with the mean pretest score increasing from 62.4 to 84.7 in the posttest. The N-Gain score was 0.59 (moderate category), and the t-test result showed statistical significance (p < 0.05). Therefore, the developed contextual-based mathematics learning model is considered valid, practical, and effective in improving elementary school students’ numeracy literacy.